The impact of tropical storm Ondoy on Marikina Polytechnic College Library with implications on the development of a disaster plan - Balquiedra, John Patrick M.; Buenrostro-Cabbab, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Disasters can occur in different forms. A disaster in the library is an unforeseen event which puts collection at risk. Natural disasters cannot be prevented, but measures can be taken to eliminate or reduce the possibility of damages. The Philippines is very prone to different kinds of hazards. Each year, about 20 typhoons occur in the Philippine area of responsibility of which an average of 9.2 actually crosses the country. According to PAGASA (Philippine Atmospheric, Geophysical and Astronomical Services Administration), typhoons and storms bring the most damages to the country than any other natural phenomena.
On September 26, 2009, Saturday, thousands of people fled their homes as overnight rains brought by Tropical Storm Ondoy caused flooding in wide areas of Metro Manila and other provinces of the northern Philippines. In Metro Manila, at least 33 villages in San Juan, Malabon, Muntinlupa, Quezon, Makati, Pasay, Pasig, Valenzuela and Marikina Cities were flooded.
Marikina City was the area that sustained the most damages by Tropical Storm Ondoy, leaving eight out of sixteen barangays submerged in floodwaters. Due to its geographical location, the city is considered as one of the most vulnerable cities to natural disasters such as earthquake, flood, etc.
Tropical Storm Ondoy affected several libraries in Marikina City; one of these libraries is the Marikina Polytechnic College Library (MPCL), which received permanent damages on books, computers, and furniture that roughly cost up to three million pesos. Because of the damage they received from Tropical Storm Ondoy back in 2009, it was prove that the library was not ready and prepared before the storm made landfall.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Marikina Polytechnic College Library; Emergency management -- Philippines -- Marikina City